The effects of religiosity and knowledge on the perceptions and attitude of muslim doctors that influence the intentions that impact on behavior in using halal drugs in Indonesia - Tri Utami, Amalia; Wahidmurni, Wahidmurni; Walid, Muhammad (Journal of Community Medicine and Health Solutions, 2022)
Introduction: In the spirit of maintaining health and seeking medicine to cure a disease, the question of halal and haram still needs to be answered. This coincides with the words of the Prophet Muhammad SAW “Verily Allah does not make your healing in what He has forbidden you” (HR. Imam Bukhari). The purpose of this quantitative study was to determine the effect of religiosity, perception, knowledge, and attitudes of Muslim doctors on the use of halal drugs in Indonesia. Materials and methods: This quantitative research method with correlational type examines the relationship between religiosity, perceptions, knowledge, attitudes, intentions, and behaviors that are shared online using google form. Data was measured using a Likert scale. A five-point Likert scale was used for statements: Strongly Disagree: 1, Disagree: 2, Uncertain: 3, Agree: 4, and Strongly Agree: 5. The sample size used was 435 Muslim doctors. The data obtained were then processed using the SmartPLS 3.0 application. Results: The results obtained are that there is a relationship between the religiosity of Muslim doctors on perceptions so as to encourage intention so that there is a change in behavior in the use of halal drugs in Indonesia. In addition, there is a relationship between knowledge and attitudes so as to encourage intentions that cause behavioral changes in the use of halal drugs in Indonesia by Muslim doctors. In fact, every practice depends on the intention, therefore it is important to maintain the intention, which in this study is influenced by perceptions and attitudes so that charity will result in commendable behavior that is blessed by Allah SWT. In addition, there is also a need for education about halal drugs that are appropriate to be taught at the medical faculty of Islamic universities in Indonesia.